Common variants in the obesity-associated genes FTO and MC4R are not associated with risk of colorectal cancer. (October 2016) - Yang, Baiyu; Thrift, Aaron P.; Figueiredo, Jane C.; Jenkins, Mark A.; Schumacher, Fredrick R.; Conti, David V.; Lin, Yi; Win, Aung Ko; Limburg, Paul J.; Berndt, Sonja I.; Brenner, Hermann; Chan, Andrew T.; et al.
Highlights: Variants in or near FTO and MC4R genes have been associated with obesity, a convincing risk factor for colorectal cancer. We found no associations of individual variants in or near FTO and MC4R with risk of colorectal cancer. This paper is the largest and most comprehensive evaluation of obesity-related genes FTO and MC4R with colorectal cancer risk. Abstract: Background: Obesity is a convincing risk factor for colorectal cancer. Genetic variants in or near FTO and MC4R are consistently associated with body mass index and other body size measures, but whether they are also associated with colorectal cancer risk is unclear. Methods: In the discovery stage, we tested associations of 677 FTO and 323 MC4R single nucleotide polymorphisms (SNPs) 100 kb upstream and 300 kb downstream from each respective locus with risk of colorectal cancer in data from the Colon Cancer Family Registry (CCFR: 1960 cases; 1777 controls). Next, all SNPs that were nominally statistically significant (p < 0.05) in the discovery stage were included in replication analyses in data from the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO: 9716 cases; 9844 controls). Results: In the discovery stage, 43 FTO variants and 18 MC4R variants were associated with colorectal cancer risk (p < 0.05). No SNPs remained statistically significant in the replication analysis after accounting for multiple comparisons. Conclusion: We found no evidence that individual variants in or near the obesity-related genes FTO and MC4R are associated with risk of colorectal cancer.